100 years on: the impact of the discovery of insulin on clinical outcomes. Issue 1 (16th August 2021) - Buse, John B; Davies, Melanie J; Frier, Brian M; Philis-Tsimikas, Athena
Abstract : Throughout history, up to the early part of the 20th century, diabetes has been a devastating disorder, particularly when diagnosed in childhood when it was usually fatal. Consequently, the successful pancreatic extraction of insulin in 1921 was a miraculous, life-changing advance. In this review, the truly transformative effect that insulin has had on the lives of people with type 1 diabetes and on those with type 2 diabetes who are also dependent on insulin is described, from the time of its first successful use to the present day. We have highlighted in turn how each of the many facets of improvements over the last century, from advancements in the properties of insulin and its formulations to the evolution of different methods of delivery, have led to continued improvement in clinical outcomes, through the use of illustrative stories from history and from our own clinical experiences. This review concludes with a brief look at the current challenges and where the next century of technological innovation in insulin therapy may take us.